Direct enantioselective C-acylation for the construction of a quaternary stereocenter catalyzed by a chiral bicyclic imidazole. Issue 8 (11th January 2017) - Wang, Mo; Zhang, Xiao; Ling, Zheng; Zhang, Zhenfeng; Zhang, Wanbin
Abstract : A direct enantioselective C -acylation of benzofuranones was developed using a chiral bicyclic imidazole catalyst and an achiral tertiary amine additive. Abstract : A direct enantioselective C -acylation of 3-substituted benzofuran-2(3 H )-ones (with up to 97% ee) was developed using a chiral bicyclic imidazole catalystOAc-DPI and an achiral tertiary amine additive DIPEA. The reaction mechanism for the direct C -acylation has been investigated using both experimental and theoretical studies.